Particle-hole asymmetry in the dynamical spin and charge responses of corner-shared 1D cuprates - Shaozhi Li (Nature Portfolio, 2021)
The underlying mechanism of the superconductivity in high-Tc cuprates and the role spin and charge excitations play has been under debate since the cuprates were first discovered. Here, the authors perform a series of calculations for multi- and single-orbital model of a 1D cuprate system revealing the importance of oxygen degrees of freedom and their relevance to resonant inelastic x-ray scattering experiments.